Safety and Efficacy of Two Different Concentrations of Ketamine and Propofol Combinations in Cataract Surgery: A Double-blind Randomized Clinical Trial: - Shafa, Amir; Heydari , Seyed Morteza; Shetabi, Hamidreza; Peyman, Alireza; Najafiani, Maryam (Galen Medical Journal, 2022)
Background: Due to the importance of appropriate sedation and immobility of the patient in cataract surgery, this study was performed to compare the safety and efficacy of a combination of ketamine and propofol (ketofol) in two different ratios. Materials and Methods: This double-blind, randomized clinical trial was carried out on patients who underwent cataract surgery in Feyz Hospital, Isfahan, Iran. Patients were randomly divided into group I (n=30, ketamine/propofol 2:1 ratio) and group II (n=30, ketamine/propofol 4:1 ratio). The quality of sedation (using Ramsay sedation scale [RSS]), cardiovascular parameters such as systolic blood pressure (SBP), diastolic blood pressure (DBP), arterial blood pressure, SPO2, and heart rate, as well as patient and surgeon satisfaction, were evaluated in both groups. Results: The SPO2 and heart rate were significantly lower and higher in group I than in group II during various surgery times, respectively (P=<0.0001 for both comparisons). In terms of patient and surgeon satisfaction, it was found that no patient was dissatisfied with the sedation status in group II, while four patients (13.3%) in group I were dissatisfied (P=0.005). However, RSS, SBP, and DBP were significantly different between the two groups (P>0.05 for all comparisons). Conclusion: It seems that the use of lower ketamine doses in combination with propofol (4:1) is a safe and preferable option to provide sedation in cataract surgery.